Inovasi Alat Ukur Multiparameter Kualitas Air Berbasis Android: Indonesia - Siswoyo, Eko; Azis, Muhammad Turmudzi Abdul (UII, 2024)
The existence of clean water on this earth is very necessary to support the lives of humans and other living creatures. Sustainable management of clean water sources is necessary to ensure that the quality meets certain requirements or quality standards, which often becomes a problem, especially regarding measurement methods that require a long time and are quite expensive. This condition demands innovation in water quality measurement methods that are fast, accurate and cheap. The aim of this research is to examine the accuracy of an Android-based water quality measuring tool using a smartphone, especially the parameters of temperature, turbidity, Total Dissolved Solid (TDS), pH and conductivity simultaneously. The method used in this research is that prepared water samples are measured using an Android-based multi-parameter measuring tool developed in this research. The results of repeated testing at least ten times for each parameter are compared with the measurement results of calibrated measuring instruments available on the market, then statistical tests are carried out to see the performance of the measuring instruments that have been developed. The results of this research show that for all test parameters using this measuring instrument the values ​​are very close to the measurement results using the manufacturer's measuring instruments that are commonly used. It is hoped that the results of this innovation will be an alternative choice for measuring several water quality parameters accurately, quickly, easily and cheaply based on Android and be able to overcome environmental problems in the future.